Infant Ross-Konno, Endocardial Fibroelastosis Resection and Mitral Valve Repair. Issue 3 (May 2022) - Najm, Hani; Gupta, Sohini; Weingarten, Noah; Stewart, Robert; Ahmad, Munir; Lane, John; Amdani, Shahnawaz; Karamlou, Tara
Optimal management of critical aortic stenosis (AS) in infants depends on the left ventricle's (LV's) ability to maintain adequate output. Determining feasibility of biventricular repair may be difficult, particularly in those with mitral disease, endocardial fibroelastosis (EFE), multi-level obstruction, and uncertain physiologic capacity. We report a case of a three-month-old with critical AS, severely reduced LV function, EFE, and moderate mitral regurgitation (MR), who underwent a Ross-Konno procedure with concomitant EFE resection and mitral valve repair. Although the technical sequence is challenging, definitive surgery completely relieved multi-level obstruction and MR with markedly improved LV function.